Implementasi REPVIT (Role Play Virtualitation) pada Model POSBINDUS (Pos Bimbingan Terpadu Stunting) sebagai Pendeteksi Awal Kasus Stunting - Fahrini Yulidasari; Atikah Rahayu; Muhammad Irwan Setiawan (Jurnal Abdimas Kesehatan (JAK), 2022)
Repvit (Role Play Virtualitation) is an intervention effort to overcome the problem of stunting by providing nutrition education to cadres, because the situation of adapting to new habits in the Covid-19 era requires personnel who can directly move the community as the spearhead of health services at the household and village levels, not forming too many crowds in the community as part of the anticipation of preventing the transmission of covid-19, so that the implementation of Repvit for cadres can effectively prevent stunting toddlers in the Alang River area. The Alang River is one of the riverbank areas in the Banjar Regency area, most of the residents make a living as farmers in the cultivation of ponds, ponds, karamba, rice fields/rice fields and floating nets. This condition makes the Alang River one of the areas that are able to provide the region's food needs from these natural products. Based on data from the Health Office of South Kalimantan Province, it is known that the highest prevalence of stunting is in the Banjar Regency area. Most of the work of mothers as housewives and fathers as fish farmers. With this background and characteristics, the purpose of the service is the implementation of repvit (role play virtualization) aimed at cadres of the Alang River area. The results of educating cadres, obtained differences in knowledge before and after education about stunting, causal factors, and local food modification skills.